Effects of Some Antihypertensive Drugs on the Metabolism and Pharmacokinetics of Indapamide in Rats - Fang Yan; Ying Hu; Bin Di; Ping Lei He; Guibin Sun (Frontiers Media S.A., 2012)
Purpose. Indapamide, a non-thiazide antihypertensive diuretic agent, has been widely coadministered with other classes of antihypertensive agents to reach target systolic blood pressure. Indapamide is extensively metabolized by cytochromes P450. Interaction of indapamide and other antihypertensive drugs are unknown. We investigated the effects of other antihypertensive drugs on the metabolism and pharmacokinetics of indapamide in vitro and in vivo. Methods. Indapamide metabolism was studies in vitro using human liver microsomes pretreated with or without different concentrations of CYP-selective inhibitors and seven major antihypertensive drugs, felodipine, nifedipine, nitrendipine, telmisartan, irbesartan, valsartan and puerarin. Furthermore, the pharmacokinetics of indapamide was determined by HPLC-MS/MS to evaluate the effects of felodipine coadministered on the bioavailability of indapamide in rats in vivo. Results. The Km and Vmax of indapamide metabolism were 114.35 ± 3.47 μM and 23.13 ± 6.61 μmol/g/min. The metabolites of indapamide, hydroxyl-indapamide and dehydrogen-indapamide, were followed. CYP3A4 and CYP2C19 were involved in indapamide metabolism in human live microsomes. In addition, felodipine, nifedipine and nitrendipine significantly inhibited indapamide metabolism with the maximum inhibitory rates of 82.6%, 72% and 95%, respectively. Felodipine significantly elevated indapamide plasma concentration and prolonged its half-life. Conclusions. Combination therapy of indapamide and felodipine might lead to the alteration of indapamide metabolism and pharmacokinetics. The consequence of such an interaction that may include increased effectiveness and side effect needs to be tudeis in human. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.